Quality and Variability of Online Physical Therapy Protocols for Isolated Meniscal Repairs - Trofa, David P.; Parisien, Robert L.; Noticewala, Manish S.; Noback, Peter C.; Ahmad, Christopher S.; Moutzouros, Vasilios; Makhni, Eric C. (The Journal of Knee Surgery, 2019)
The ideal meniscal repair postoperative rehabilitation protocol has yet to be determined. Further, patients are attempting to access health care content online at a precipitously increasing rate given the efficiency of modern search engines. The purpose of this investigation was to assess the quality and variability of meniscal repair rehabilitation protocols published online with the hypothesis that there would be a high degree of variability found across available protocols. To this end, Web-based meniscal repair physical therapy protocols from U.S. academic orthopaedic programs as well as the first 10 protocols identified by the Google search engine for the term “meniscal repair physical therapy protocol” were reviewed and assessed via a custom scoring rubric. Twenty protocols were identified from 155 U.S. academic orthopaedic programs for a total of 30 protocols. Twenty-six protocols (86.6%) recommended immediate postoperative bracing. Twelve (40.0%) protocols permitted immediate weight-bearing as tolerated (WBAT) postoperatively, while the remaining protocols permitted WBAT at an average of 4.0 (range, 1–7) weeks. There was considerable variation in range of motion (ROM) goals, with most protocols (73.3%) initiating immediate passive ROM to 90°. The types and timing of strength, proprioception, agility, and pivoting exercises advised were extremely diverse. Only five protocols (16.7%) employed functional testing as a marker for return to athletics. The results of this study indicate that only a minority of academic orthopaedic programs publish meniscal repair physical therapy protocols online and that within the most readily available online protocols there are significant disparities in regards to brace use, ROM, weight-bearing, and strengthening and proprioception exercises. These discrepancies reflect the fact that the best rehabilitation practices after a meniscal repair have yet to be elucidated. This represents a significant area for improved patient care through standardization.
Keywords: meniscus repair; rehabilitation; physical therapy